Art and cultural tourism for sustainable income: a conceptual framework for senior citizen centres in Malaysia - Mohammad Mazani, Nor Zhafira Adlina; Abdul Aziz, Mohd Nasiruddin; Ibrahim, Nur Hisham; Ramlie, Mohd Khairulnizam; Dzulkifly, Najat Affendy (Universiti Teknologi MARA, Perak, 2025)
This paper proposes a conceptual framework that fully integrates the Triple Bottom Line (TBL) and Socio-Ecological Model (SEM) as it examines just how art and cultural tourism initiatives are able to support senior citizen centres throughout Malaysia in order to generate sustainable income. The framework identifies five factors, which is Social Engagement, Economic Growth, Environmental Effects, Operational and Technology. In order to assess each of the positive effects that each factor has had on income sustainability, some hypotheses are developed. An inclusive mixed-methods approach is proposed, a combination of quantitative surveys and regression analysis with qualitative thematic interviews. The expected results is a replicable empowerment model to guide cultural tourism as practical income strategy for senior centres, carefully balancing financial viability, social well-being, as well as environmental stewardship.